2022
DOI: 10.3390/ijms232214496
|View full text |Cite
|
Sign up to set email alerts
|

Soluble PD-L1 as a Prognostic Factor for Immunotherapy Treatment in Solid Tumors: Systematic Review and Meta-Analysis

Abstract: Blocking the Programmed Cell Death Protein 1 (PD-1)/programmed death ligand-1 (PD-L1) axis has demonstrated great efficacy in cancer immunotherapy treatment and remains the central modality of immune targeting. To support the rational and tailored use of these drugs, it is important to identify reliable biomarkers related to survival. The role of the soluble form of the PD-L1 (sPD-L1) as a prognostic biomarker related to survival in solid cancer patients treated with immunotherapy has not yet been consistently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…The results showed that preoperative patients with NSCLC had lower levels of sICOS, which might result in a reduced ability to provide important co-stimulatory signals to enhance and maintain T-cell responses in antitumor immunity. Although studies have shown that the sPD-L1 level can be used as a potential biomarker for lung cancer screening and staging prediction 47 , high levels of sPD-L1 are associated with poorer survival in patients with NSCLC 48 . In the present study, sPD-L1 did not differ according to the clinicopathological classification of patients with NSCLC, which was consistent with the study of Li et al 49 .…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that preoperative patients with NSCLC had lower levels of sICOS, which might result in a reduced ability to provide important co-stimulatory signals to enhance and maintain T-cell responses in antitumor immunity. Although studies have shown that the sPD-L1 level can be used as a potential biomarker for lung cancer screening and staging prediction 47 , high levels of sPD-L1 are associated with poorer survival in patients with NSCLC 48 . In the present study, sPD-L1 did not differ according to the clinicopathological classification of patients with NSCLC, which was consistent with the study of Li et al 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in different studies, sPD‐L1 cut‐off values varied widely, contributing to heterogeneity 176 . As well, previous molecular signatures and therapies from different types of cancer could affect sPDL‐1 release 177 . Thus, future prospective studies using standard assessment methods should be performed to determine and validate the optimal cut‐off value as well as prognostic value regarding immunotherapy efficacy in different solid tumor settings.…”
Section: Soluble Systemic Markers Of Immunotherapymentioning
confidence: 99%
“…However, when accounting for other clinical factors in multivariable analyses, only soluble PD-L1 expression levels remained associated with progression-free survival for these patients 33. Higher circulating soluble PD-L1 expression was also associated with decreased overall and progression-free survival in a meta-analysis of patients with cancer at different anatomical sites, including non-small cell lung cancer and melanoma patients who had been treated with immunotherapy 34. In contrast, although low serum exosomal PD-L1 expression was associated with increased median overall survival for pancreatic ductal adenocarcinoma patients compared with those with high exosomal PD-L1 expression, there was little statistical evidence to support this observed difference 35.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, although low serum exosomal PD-L1 expression was associated with increased median overall survival for pancreatic ductal adenocarcinoma patients compared with those with high exosomal PD-L1 expression, there was little statistical evidence to support this observed difference 35. Therefore, even though the prognostic roles of circulating PD-1 and PD-L1 expression levels have not been fully determined, there is some evidence supporting an association between blood-based measures of these immune checkpoint proteins and cancer survival, and the mechanism of action of these drugs is mediated by T cells 33–35…”
Section: Introductionmentioning
confidence: 99%